MENINGKATKAN KEMAMPUAN BAHASA INGGRIS SISWA DALAM MENULIS KALIMAT INFORMATIVE MELALUI MODEL PEMBELAJARAN W2C PADA SMA NEGERI 2 RAMBAH HILIR KABUPATEN ROKAN HULU - Hasibuan, Parman (Universitas Pasir Pengaraian, 2016)
Learning Processes has to be developed in the efforst of searching for the proper techniques to solve students’ learning problems. The technique of W2C is one of the alternatives. This was showed by the results of the study of minimizing students’handicaps in writing information about something even a very simple one, like what is a pen? The results of the study revealed that in the first cycle the highest score was 78 which was increased to 81,33 in the second cycles, and then 87,33 in the third one.The lowest score 50 in the first cycle increased to 70 in the second cycle, and then 71,33 in the third. The average scores ranged from 72,912 in the first to 76,146 in the second, and then 77,58 in the third cycles. In line with the percentage of development of students’ learning competence using the Model of W2C learning, the scores below 70 was 93,33% at first, but finally every students had achieved the target scores(100%). For all colleaques teachers, it is expected to innovate their teaching quality by having various teaching teachniques in the teaching processes.